Study shows wrong people, wrong skills, wrong tools - Petty, Duncan R; Zermansky, Arnold (BMJ, 2007)
Salter et al identify some deficiencies in a small sample of pharmacist consultations. 1 Their results say more about the need for consultation skills training and the context of the pharmacists and patients involved in this study than they do about the concept of pharmacist medication review.